Teaching English Language in Early Grades - YADAV, PADMA (THE PRIMARY TEACHER, 2014)
Language learning is very important for children since it provides the foundation for all later learning. This paper supports children learning English as a second language in early years. It has a particular focus on children in three to six years age group and supports children’s transition in school. This paper is an outcome of learning that happened during the three months of field visit in rural Anganwadi centres and government primary school of Haryana State, India. The study provides information about second language learning among young children from three to six years and children in early grades. It was found that children can learn new language easily say English with support, encouragement and by providing the print rich and spoken environment.